Trend Trends and Gaps in Marital Satisfaction Research in Indonesian Psychology: A Systematic Review (2019-2024) - Deassy M Destiani; Rita Eka Izzaty; Herwin Herwin (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Marital instability often leads to dissatisfaction and may result in divorce. In Indonesia, around 400,000 divorces occur annually, reflecting persistent marital dissatisfaction. This study aims to identify research gaps in the study of marital satisfaction within Indonesian psychology literature from 2019 to 2024. Using a qualitative descriptive method, the study conducted a systematic content analysis of 101 journal articles retrieved via Google Scholar using Publish or Perish 8. Results show a generally increasing trend in research despite a temporary decline in publication numbers. Most studies employed quantitative methods (76.53%), correlational designs (72.37%), and focused on variables such as religiosity (12.36%). The most frequently used instrument was the ENRICH Marital Satisfaction scale (32.61%), with correlation analysis as the dominant statistical method (31.07%). The results of this study highlight prevailing trends in existing research and identify several areas requiring further investigation to enhance understanding of marital satisfaction in Indonesia. Keywords: marital satisfaction, religiosity, ENRICH Marital Satisfaction Scale, research trends, Indonesia